Kinerja Keuangan Perusahaan Metal yang Terdaftar di Bursa Efek Jakarta Aplikasi Cash Flow Ratios Analysis - Tulasi, Daniel (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
The cash flow ratios analysis is an analytical method to assess corporate performance, especially the financial performance with the focus on corporate cash flows. This study is aimed at (1) evaluating whether, simultaneously the cash flow variables (ratios) can significantly distinguish the firm with a healthy financial performance from that without; (2) determining whether the discriminate value obtained from cash flow ratios model can be used as a basis for distinguishing the firm with a healthy financial performance from that without; and (3) determining the most significant variable distinguishing the financial performance of the metal industries. The result of the study indicate that: (1) simultaneously, the cash flow ratios had significant influence (2) the discriminate value (Z-score) can be used as a criterion to distinguish the firm, and (3) the ratios of cash flow were the most significant variables in distinguishing the firm with a healthy financial performance from that without.